Green Marketing Through Social Media On Generation Z's Purchase Intention With Environmental Awareness As A Mediation - Siti Lia Syari; Muhi Mukti; Pipin Suryanisari (JURNAL ECONOMINA, 2026)
This study will examine how the purchase intention of Generation Z in Lebak Regency is influenced by green marketing through social media and environmental awareness . The structural equation model based on partial least squares structural equation modeling (SEM-PLS) is a quantitative method used in this study. One hundred respondents were randomly selected to be the sample. Thus, green marketing through social media has a significant positive influence on purchase intention . Green marketing through social media significantly increases environmental awareness . In addition, purchase intention is not influenced by environmental awareness , either positively or negatively. In green marketing through social media, purchase intention is not directly influenced by environmental awareness . The results indicate that increased environmental awareness is not automatically followed by a tendency to purchase green products . This study contributes to business actors in developing green marketing strategies through social media.